A inclusão do aluno surdo no ensino regular na perspectiva de professores da rede municipal de ensino de Botucatu - Tenor, Ana Claudia (2008)
The inclusion of hearing impaired children in regular classrooms has been thoroughly discussed from different perspectives including legal, human rights, oral or sign language, and special education. However, there have been few studies approaching the teachers knowledge and attitudes towards inclusion. Therefore, the goal of the present study was to investigate how the policy of inclusion and its implementation has been practiced and experienced by nursery and elementary school teachers of Botucatu s school system. Teachers of two of the system s schools (one nursery and 1 elementary) participated in the study. A qualitative approach was chosen, specifically group dynamic using a poster with related themes to trigger the discussion. The group dynamics were audio recorded and the dialogues transcribed for further analysis. The dada was analyzed following a method of category construction. The results have shown that teachers are not aware of the need for a common language, with or without an interpreter, to enable different classrooms dynamics. Aiming at being understood by the children, teachers tend to improvise different communicative resources. In general, they tend to place great value in efforts of communication, regardless abilities in a specific language, demonstrating very low expectations in relation to child s learning and literacy. Furthermore, they base their pedagogical practice based on the conception of language as a code, solely used for information exchange. Finally, teachers point at lack of family involvement and deficiency in the preparation of teachers and school in the inclusion process